6q2.31q23.3 Interstitial Deletion: A Rare Prenatal Diagnosis - Palmeira, Beatriz; Torrão, Maria Manuel; Ferreira, Manuela (Brazilian Journal of Case Reports, 2025)
Interstitial deletions in the proximal region of the long arm of chromosome 6 are a rare finding, and only a few cases were published. The severity of the condition and the signs and symptoms depend on the size and location of the deletion and which genes are involved. These cases are mainly diagnosed with children or adults presenting various signs and symptoms, such as intellectual disability, developmental delay, growth retardation, cardiac anomalies, and dysmorphic features. Its diagnosis at a prenatal level is an even more rare finding. We present a case of a 29-year-old pregnant woman who was submitted to a chorionic villus biopsy due to a nuchal translucency above the 99th centile. The Array Comparative Genomic Hybridization revealed a pathogenic interstitial deletion of the chromosome 6 at 6q22.31q23.3, involving the EYA4 gene. We present a case of a 29-year-old pregnant woman who was submitted to a chorionic villus sampling due to a nuchal translucency above the 99th centile. The Array Comparative Genomic Hybridization revealed a pathogenic interstitial deletion of the chromosome 6 at 6q22.31q23.3, involving the EYA4 gene.